REKAYASA EKSPRESI GEN PEMBUNGAAN Hd3a DIBAWAH KENDALI PROMOTER ROL C PADA JARAK PAGAR (Jatropha curcas L.) - Sulistyaningsih, Yohana C; Hartana, Alex; Widyastuti, Utut; Hamim, Hamim; Suharsono, Suharsono (BERITA BIOLOGI, 2011)
Flowering in jatropha (Jatropha curcas L.) was considered as one of major factors that contribute to its productivity. Small number of female flowers produced in each inflorescence was believed as the main cause of low seed production.Introduction of Hd3a flowering gene driven by rol C promoter was supposed to improve total number of flowers including female flower.The objective of this research was to optimize cell proliferation and regeneration medium in Jatropha transformation method mediated by Agrobacterium, to obtain transgenic Jatropha containing Hd3a flowering gene as well as to understand the effect of this transgene on jatropha flowering character.Callus induction medium containing 0.5 mg/1 IBA added with 3 g/1 PVP produced the highest frequency of shoot formation.We obtained 26.67% to 33.33% putative transgenic plantlets that were able to grow in 40mg/l hygromycin selection medium. PCR analysis revealed that seven out of 10 putative transgenic plantlets were positively transgenic.Extremely early flowering character that was confirmed by histological analysis was also shown by some transgenic plantlets.